Saddle-nose and bilateral cauliflower ear deformities with pyoderma gangrenosum-like ulcers, cavitary pulmonary lesions, digital gangrene and pulselessness in a young female - Subhadarshani, Sweta (BMJ Case Rep, 2017)
We report a young female who presented with saddle-nose and bilateral cauliflower ear deformities along with pyoderma gangrenosum-like ulcers, digital gangrene and pulselessness. Subsequently, she was found to have bilateral conductive hearing loss, a corneal opacity, mild aortic regurgitation and radiological evidence of cavitary changes in lungs and aortoarteritis. Our patient had a constellation of symptoms which posed a diagnostic challenge. Finally, a diagnosis of relapsing polychondritis with several unusual features was made. Overlap with Takayasu’s arteritis and granulomatosis with polyangitis, which has been reported rarely in the literature, cannot be excluded.